Developing Ethics for 'Santri' Empowerment: The Case of the Pesantren al-Falah of Gorontalo, Indonesia - Kango, Andries; Perdana, Dian Adi; Biya, Sriyuni Regita (Jurnal Pemberdayaan Masyarakat: Media Pemikiran dan Dakwah Pembangunan, 2021)
The failure of community empowerment often forgets the ethics of change-makers as an essential instrument in program implementation. This assumption is existed because of weak human development resources in an educational institution in terms of shaping character. Pesantren or Islamic Boarding School offers another alternative to transforming santri or student ethics effectively when taking action in society. This article aims to explore the strategy of developing student ethics in the process of social transformation. The research data was generated through observation method at Al-Falah Islamic boarding school in Gorontalo, in-depth interviews with caregivers, teacher councils, students, and documentation related to development to shape students' character. Al-Falah Islamic boarding school has responded to modernity issues and implemented them into learning practices. This pesantren chooses three strategies (sentimental, rational, and takziyah) to develop the ethical quality of students. The fundamental Islamic values or ahklakul karimah (ethical values) is chosen because it can be primary guidelines for change-makers in developing community empowerment activities. In line with this, this research suggests that this strategy can be implemented in pesantren and in different contexts elsewhere. However, because limitation of the research, the ethical values are impossible to test in various aspects, so it is necessary to consider updated survey studies to prove the suitability of ethics and the achievement of community empowerment programs.